Comparative clinical outcomes of Taiwanese patients with resected buccal and tongue squamous cell carcinomas. (April 2017) - Liao, Chun-Ta; Wen, Yu-Wen; Yang, Lan Yan; Lee, Shu Ru; Ng, Shu-Hang; Liu, Tsang-Wu; Tsai, Sen-Tien; Tsai, Ming-Hsui; Lin, Jin-Ching; Chen, Peir-Rong; Lou, Pei-Jen; Wang, Cheng Ping; et al.
Highlights: Large-scale studies on the clinical outcomes of buccal SCC are still lacking. Patients with buccal SCC had a higher frequency of p-Stage IV than tongue SCC. However, survival of patients with buccal SCC was slightly better than tongue SCC. The survival advantage for buccal SCC is significant in large sample sizes. Abstract: Objectives: Although patients with buccal squamous cell carcinoma (SCC) usually show acceptable outcomes, local control and survival rates are generally lower than those observed for tongue SCC. This study was designed to compare the clinical outcomes of Taiwanese patients with these two common oral cavity malignancies. Methods: Patients with first primary buccal or tongue SCC who were included in the Taiwanese Cancer Registry Database between 2004 and 2012 were eligible. The study sample consisted of 16, 379 patients (7870 buccal SCC and 8509 tongue SCC) who received surgery with or without adjuvant therapy. The 5-year disease-specific survival (DSS) and overall survival (OS) rates served as the outcome measures. Results: Compared with tongue SCC, patients with buccal SCC had a higher prevalence of males (95.7% vs. 86.4%, p < 0.0001), pT4 disease (21.4% vs. 12.7%, p < 0.0001), and p-Stage IV (30.4% vs. 24.8%, p < 0.0001) but a lower frequency of pN2 disease (15.2% vs. 18.5%, p < 0.0001). The 5-year DSS and OS rates of buccal SCC patients were slightly higher than those of tongue SCC (78% vs. 77%, p = 0.0297; and 71% vs. 69%, p = 0.0231, respectively). Multivariate analysis identified tumor site (tongue vs. buccal SCC), sex (male vs. female), age (≥65 vs. <65 years), pT classification (T4/T3/T2 vs. T1), and pN classification (N3/N2/N1 vs. N0) as independent prognostic factors in the entire study cohort. Conclusions: The survival advantage of buccal SCC over tongue SCC appears significant in large clinical samples, despite a higher prevalence of p-Stage IV disease in the former.